GAMBARAN TINGKAT DEPRESI, KECEMASAN DAN STRESS KERJA PADA GURU MTsN 1 SOLOK SELATAN - Nofrianti, Ade Ria; Waldani, Dina (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Work stress is a pressing feeling or feeling of pressure experienced by employees in dealing with their work. MTsN 1 Solok Selatan is one of the public schools. Based on the results of brief interviews with several teachers, the teacher said they were stressed and confused because there were demands for tasks that had to be prepared, such as preparing administrative completeness, changing curricula. This type of research is descriptive research. The sample used in this study were 65 people. The measuring tool for this research is a questionnaire by distributing questionnaires. The conclusion from the results of the study is that the level of teacher work stress is normal (46.2%), mild stress gets results (16.9%), moderate stress (20.0%) and severe stress gets results (16.9%). Suggestions to teachers and schools namely Regulating diet and exercise, Getting out of temporary routines, Annual recreation with teachers and students, Support from family and friends, Increasing the intensity of worship, Working meetings in tourist spots, Giving awards in the form of crowning outstanding teachers and having cooperation and deliberation between subject teachers at school or in the MGMP.